2021
DOI: 10.1101/2021.10.19.464963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupil Dilation and Response Slowing Distinguish Deliberate Explorative Choices in the Probabilistic Learning Task

Abstract: This study examined whether pupil size and response time would distinguish directed exploration from random exploration and exploitation. Eighty-nine participants performed the two-choice probabilistic learning task while their pupil size and response time were continuously recorded. Using LMM analysis, we estimated differences in the pupil size and response time between the advantageous and disadvantageous choices as a function of learning success, i.e., whether or not a participant has learned the probabilis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…Crucially, the magnitude of a large-scale β suppression, when a subject formed his/her decision reliably, predicted decision costs (with response time taken as a measurable proxy of this internal variable) on a single trial basis. Given multiple evidence associating the strength of β suppression with greater cognitive and attentional efforts 1618 , this finding strongly suggests that such a choice requires additional resources to overcome the internal utility model favoring the advantageous alternative and strongly supports the hypothesis of its deliberately explorative nature 13,33 .…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Crucially, the magnitude of a large-scale β suppression, when a subject formed his/her decision reliably, predicted decision costs (with response time taken as a measurable proxy of this internal variable) on a single trial basis. Given multiple evidence associating the strength of β suppression with greater cognitive and attentional efforts 1618 , this finding strongly suggests that such a choice requires additional resources to overcome the internal utility model favoring the advantageous alternative and strongly supports the hypothesis of its deliberately explorative nature 13,33 .…”
Section: Discussionsupporting
confidence: 58%
“…This conflict arises between at least two simultaneously active competing internal models, or ‘task sets’ 9,12 – one being a predominant response tendency (exploitation), and the other – its conscious alternative (exploration). Our recent pupillometric study lends support to this assumption 13 : we found that such explorative choices compared to exploitative ones are accompanied by larger pupil dilation and longer decision time. We speculated that this state of conflict supposedly entails an increase in the degree of processing required to make the deliberately explorative decisions.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations